Elemental profiling of toxic and modern primers using ICP-MS, SEM-EDS, and XPS: an application in firearm discharge residue investigation - Yüksel, Bayram; Şen, Nilgün; Ögünç, Gökhan Ibrahim; Erdoğan, Ayşegül (Australian journal of forensic sciences, 2023)
The characterization of firearm discharge residue (FDR) as a piece of evidence plays an essential role in interpreting the forensic cases involving the use of firearms, such as robberies, murders, suicides, and serious attacks. In the last decade, modern or non-toxic primers have emerged due to environmental issues. Forensic examination of gunshot residue (GSR) has become challenging as primer compositions now vary greatly. The goal of this paper is to provide the elemental profiling of both toxic and lead-free cartridge primers available in the Turkish ammunition market. Inductively coupled plasma-mass spectrometry (ICP-MS), scanning electron microscopy coupled with energy-dispersive X-ray analysis (SEM-EDS), and X-ray photoelectron spectroscopy (XPS) were used in this investigation. Multivariate statistical methodologies such as principal component analysis (PCA) and Pearson's correlation coefficient (PCC) analysis were used to interpret the elemental profile data determined in the residue generated after ignition of the cartridge primers. Three components were observed: Ba-Sb-Pb-Cu-Gd, Ti-Sr-Zn, and Al-Ca-Ga, which is also consistent with the PCC analysis. SEM-EDS was employed to confirm the existence of GSR particles. The binding energies, determined using XPS, indicated the chemical state assignments in samples such as Pb(NO 3 ) 2 , Sb 2 S 3 , Ba(NO 3 ) 2 , CuO, ZnO and MoS 2 . This research will improve the robustness of the interpretation of GSR-related evidence.